2021
DOI: 10.21037/tcr-20-3158
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of AQP9 and its value in hepatocellular carcinoma

Abstract: Background: The mortality rate for liver cancer is high worldwide. The etiology of liver cancer has altered with the high incidence rate of non-alcoholic fatty liver disease (NAFLD) although effective vaccination strategies have been developed. Therefore, it is important to discover new biomarkers for diagnosis and prognosis. Aquaporin 9 (AQP9) has been reported in some cancers, especially in liver cancer, although its role in this malignancy remains to be clarified. In this study, we conducted a bioinformatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…They are considerably small (26–34 kD) and very hydrophobic, with intrinsic membrane proteins, and AQP9 specifically contains two additional peptide spans compared to the other subtypes. The AQPs family is found in the plasma membranes of various cells and functions to transport fluid across the cell membrane [ 32 ]. In a study that aimed to obtain and characterize a dataset of significant DEGs of treatment naïve UC patients compared to healthy controls, 1480 DEGs were found in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…They are considerably small (26–34 kD) and very hydrophobic, with intrinsic membrane proteins, and AQP9 specifically contains two additional peptide spans compared to the other subtypes. The AQPs family is found in the plasma membranes of various cells and functions to transport fluid across the cell membrane [ 32 ]. In a study that aimed to obtain and characterize a dataset of significant DEGs of treatment naïve UC patients compared to healthy controls, 1480 DEGs were found in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the primary hepatic cancer burden pertains to HCC, with liver cancer representing the sixth most common oncologic condition and the second-leading cause of death from malignant neoplasm around the world [ 99 ]. AQP9 was shown to be consistently downregulated in HCC tissues and cells compared to normal liver tissues and hepatocyte cell lines, respectively [ 30 , 31 , 32 , 33 , 34 , 35 ]. Interestingly, AQP9-overexpressing human HCC SMMC-7721 cells displayed increased expression of E-cadherin and decreased expression of N-cadherin in vitro and in xenografted tumors that were positively correlated with decreased levels of phosphoinositide 3-kinase (PI3K) and p-Akt.…”
Section: Potential Relevance Of Aqp9 As Clinical Biomarkermentioning
confidence: 99%
“…The microRNAs mir-23a-3p and mir-330-3p were correlated with AQP9 inhibition upon HCC. Moreover, AQP9 was shown to be critical in tumor immunity in liver cancer [ 32 ].…”
Section: Potential Relevance Of Aqp9 As Clinical Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that AQP9 is a promising biomarker in CD patients 12 , 67 , 68 . Interestingly, AQP9 has also been reported as a prognostic indicator of many cancers in recent years and is related to immune infiltration 69 72 . Similar to CD, AQP9 expression is significantly increased in colon cancer 69 .…”
Section: Discussionmentioning
confidence: 99%